Taxonomic updates of Cheilanthes Sw. (Pteridaceae) in Peru, with a conservation assessment for four endemics - Rivera, Soledad (2024)
In its most recent concept, the genus Cheilanthes encompasses three clades distributed across South America, Africa, and Australasia. Previous studies in Peru recorded 23 species; however, advancements in molecular systematic have led to the segregation of eight of them into at least three genera. In this study, 15 species are recognized in the Peruvian flora based on the examination of 459 herbarium and field specimens, and the evaluation of morphological characters using 131 specimens. The affinities among the lineages proposed in this study are consistent with recent phylogenetic hypotheses, wherein Cheilanthes species in Peru are members of two clades, the South American and the Australasian-South American, with taxonomically important characters being the shape of rhizomatous scales and types of frond indumentum (scales, microscales, scuamules, and hairs). We found that the genus Cheilanthes is present in 20 departments of Peru, with most species having wide distribution in the central-southern Andean regions, four species having endemic status. Meanwhile, C. cantangensis, C. lonchophylla, and C. obducta are poorly represented in the northern region. The first two species are considered endemic and categorized as Endangered (EN), while the other two are classified as Least Concern (LC). Additionally, a taxonomic key is provided.